Post-COVID-19 Syndrome and Related Dysautonomia: Reduced Quality of Life, Increased Anxiety and Manifestation of Depressive Symptoms: Evidence from Greece - Galanis, Petros; Katsiroumpa, Aglaia; Vraka, Irene; Kosiara, Katerina; Siskou, Olga; Konstantakopoulou, Olympia; Katsoulas, Theodoros; Gallos, Parisis; Kaitelidou, Daphne (Acta medica Lituanica, 2023)
Background: Post-COVID-19 syndrome affects a significant number of SARS-CoV-2 infected individuals, even in asymptomatic cases causing several neurological and neuropsychiatric symptoms and signs. Materials and Methods: An online cross-sectional study with a convenience sample was conducted in Greece from November 2022 to January 2023. We measured the demographic and clinical characteristics of patients with post-COVID-19 dysautonomia in terms of the quality of life with the EQ-5D-3L, and anxiety and depressive symptoms by employing Patient Health Questionnaire-4. Results: The study population included 122 patients with post-COVID-19 syndrome. One out of four patients (27.8%) manifested post-COVID-19 dysautonomia, while the mean duration of COVID-19 symptoms was 11.6 months. Anxiety and depressive symptoms were worse after the post-COVID-19 syndrome (p<0.001 in both cases). A statistically significant reduction in quality of life was observed among patients after the post-COVID-19 syndrome (p<0.001 for both EQ-5D-3L index value and EQ-5D-3L VAS). Post-COVID-19 dysautonomia increased depression symptoms after developing the post-COVID-19 syndrome (p=0.02). We found a negative relationship between the duration of COVID-19 symptoms and the quality of life (p<0.001). Moreover, our results showed that depressive symptoms were more common among females after the post-COVID-19 syndrome (p=0.01). Also, the quality of life was lower among females than males (p=0.004 for EQ-5D-3L index value, and p=0.007 for EQ-5D-3L VAS). Conclusions: Our results suggest that post-COVID-19 syndrome causes a tremendous impact on the patients’ quality of life and mental health. In addition, we found that the groups most psychologically affected were patients with post-COVID-19 dysautonomia, females, and patients with a longer duration of symptoms. Policy makers should assign priority rights to vulnerable groups in future psychiatric planning. Policy measures should focus on the mental health of post-COVID-19 patients who seem to be particularly vulnerable.